The literary representation of reality - Davidsen, Helle Munkholm (Res Cogitans, 2018)
This article presents a reflection of the epistemological question of literary representation of reality. The epistemological status of literature is not obvious, because literature is fictional. Therefore, it is not evident in what way literature represents reality and to what degree the literary representation is true in the corresponding sense of the word. Through an exploration of Proust and his reflections on the same question in A la recherche du temp perdu, this article will analyse the representational question. This analysis will focus on a conflict between an essential understanding of truth, detached from the temporal reality, and a superficial referential realism. It will present an alternative phenomenological and semiotic realism, which connects the specific description in literature with a general conceptual level. In addition, the relationship between the perceptual and conceptual level will further be linked to cognitive semantics and Lakoff’s concept of cognitive models.